EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL BERBASIS GOOGLE CLASSROOM DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 1 HULU KUANTAN - Al Hafidz, Al Hafidz; Gimin, Gimin; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the level of effectiveness of using digital learning media based on google classroom in increasing student interest in learning economics at SMA Negeri 1 Hulu Kuantan. The population in this study were all students of class XI at Sma Negeri 1 Hulu Kuantan, as many as 60 people. The sampling technique is by random sampling. This research uses quantitative methods with experimental research models. Researchers use this method in order to know the level of effectiveness of the google classroom learning media in increasing student interest in learning. The design used in this study was the pretest posttest control group design or the pretest posttest control group design, namely in this design there were two groups, each of which was chosen randomly. The results showed that there were differences in the average learning outcomes of the Experiment class and the Control class. This proves that the use of google classroom digital learning media is effective in increasing students' interest in learning economics at SMAN 1 Hulu Kuantan.Keywords: Digital Learning Media, Google Classroom, Learning Interest.